Coalizão de governo e processo legislativo : controle de agenda e suas consequências na produção legislativa dos deputados - Souza, Gustavo Reis Sabbag de (Universidade Federal de São Carlos, 2017)
The objective of this work is to investigate the characteristics of the legislative production of the deputies from 1995 to 2010 and to seek indications of association between this and government coalitions. The problem is as follows: what are the characteristics of the legislative production of deputies from 1995 to 2010? Are these characteristics associated with Executive coalition qualities? The argument is that the laws of the deputies are regulatory and of high scope due to the control of the legislative agenda that the Executive Power exercises and that these characteristics does associate with the coalitions. The methodology is mixed, with a qualitative classification, quantitative descriptive analysis and the use of descriptive statistics and statistical inference methods. It was analyzed all the legislation with divided competence proposed by deputies and approved in the period from 1995 to 2010 (Projetos de lei e projetos de lei complementar), and classified according to their subject and scope. Altogether, there are 535 laws that are segregated by legislature to be compared with each other, with government coalitions and with the party of the president so that as hypotheses raised are to be checked. Finally, it is intended, from the data, to elucidate the role reserved to the parliament in the institutional regime in force in Brazil regarding the legislative production, in addition to contribute to a better understanding of the consequences of coalition presidentialism for a relationship among the powers.
Government coalition and legislative proccess : agenda control and its consequences in the legislative production of the deputies
Keywords: Coalizão de governo; Processo legislativo; Câmara dos Deputados; CIENCIAS HUMANAS::CIENCIA POLITICA